FUNGAL INFECTIONS ON SKIN (Homoeopathy for All, 2023)
Fungi usually make their homes in  moist areas of the body where skin  surfaces meet: between the toes, in  the genital area, and under the  breasts. Common fungal skin infections are caused by dermato phytes, such as Epidermophyton,  Microsporum, and Trichophyton.  Many such fungi live only in the  topmost layer of the epidermis  (stratum corneum) and do not  penetrate deeper. Strangely, fungal  infections on one part of the body  can cause rashes on other parts of  the body that are not infected. The term tinea or dermatophytosis  means fungal infection, whereas  dermatophyte refers to the fungal  organisms that cause tinea. Commonly these infections are  named for the body part affected,  including tinea corporis (general  skin), tinea capitis (ringworm of the  scalp), tinea unguium (onycho mycosis), tinea cruris (groin) and  tinea pedis (feet). Dermatophytes  require keratin for growth thus it  causes superficial infections of the  skin, hair, and nails, which are  inhospitable to other infectious  agents.
Keywords: hair; (general skin); body